How does networking stimulate the internationalisation of firms in Poland? - Marek Maciejewski; Krzysztof Wach; Agnieszka Głodowska (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2022)
The study’s objective is to verify the relationship between networking and the internationalisation of firms from Poland. Additionally, the relationship is evaluated according to the criterion of the scale and the pace of internationalisation. The article uses field research on the sample of internationalised firms from Poland (n = 355). The research methods used in the study are logistic regression and Chi–Square test of independence. Based on the literature review, we assumed that firms participating in formal and informal networks internationalise faster and on a larger scale. Our research confirmed this hypothesis. It means that networking stimulates the scale and the pace of internationalisation of firms from Poland (the case of late comers; post-emerging economy) in the same pattern as indicated in prior studies. Moreover, based on the empirical research we found that resources and entrepreneurial orientation are essential for networking. The study provides necessary focus on the networking and internationalisation for policy and managers. It enforces the creation of certain preconditions for network development and underlines the necessity of penetrating various types of networks (formal and informal).